2002
DOI: 10.1002/art.10527
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus–mediated osteoprotegerin gene transfer protects against particulate polyethylene–induced osteolysis in a murine model

Abstract: Objective. Osteoprotegerin (OPG), a natural negative regulator of osteoclastogenesis and bone resorption, may be a potential therapeutic agent for treatment of osteolysis-associated prosthetic joint loosening. Using an in vivo adeno-associated virus (AAV)-mediated gene transfer technique, this study was designed to evaluate the protective effects of OPG transgene against orthopedic wear debris-induced bone loss in a murine model of osteolysis.Methods. Bone tissue was implanted into established pouches on BALB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 34 publications
(39 reference statements)
5
67
0
1
Order By: Relevance
“…We demonstrated that an in vivo viralmediated gene transfer of osteoprotegerin (OPG), a secreted TNF receptor-related protein that neutralizes RANKL bioactivity, 6 exerted protective effects against wear debris-induced inflammatory osteolysis. 14 In this study, we utilize the same animal model to demonstrate that EM inhibits wear particle-induced osteoclastogenesis. The study generated two additional findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that an in vivo viralmediated gene transfer of osteoprotegerin (OPG), a secreted TNF receptor-related protein that neutralizes RANKL bioactivity, 6 exerted protective effects against wear debris-induced inflammatory osteolysis. 14 In this study, we utilize the same animal model to demonstrate that EM inhibits wear particle-induced osteoclastogenesis. The study generated two additional findings.…”
Section: Discussionmentioning
confidence: 99%
“…19 This model demonstrates a rapid and reproducible method to evaluate wear debris-induced osteolysis, and provides a useful tool to screen anti bone resorption compounds and other therapeutic approaches. 14,20 In the present study, we have used this model to investigate the effect of EM on UHMWPE particles-induced inflammatory osteolysis in vivo, and have demonstrated that EM inhibits UHMPWE particles-induced inflammation, osteoclastogenesis, and bone resorption.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…With this strategy, it has been proposed to use OPG in order to decrease the bone resorption when particles are present [42,43]. The delivery of OPG could be done through gene therapy [44] or could be locally delivered as it has been recently proposed to use the orthopedic implant as drug delivery system [45].…”
Section: Article In Pressmentioning
confidence: 99%
“…In the second model, osteolysis is studied in bones implanted into air pouches, which therefore lack a blood supply and are more analogous to bone organ culture experiments rather than to the in vivo situation [45,46]. Moreover, the extent of bone loss induced by particles in the air pouch model has not been described [45,46].…”
Section: Introductionmentioning
confidence: 99%